UPAYA MENINGKATKAN GERAK DASAR LARI GAWANG DENGAN PERMAINAN AREA CROSS PADA SISWA KELAS V SD NEGERI 11 JAMBU (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to apply the concept area cross by replacing the actual goal with rubber througharea cross game. This is done to reduce the fear of injury and the students will create a learning becomes fun.This type of research is a class act using metode practice test. Subject of research is student class five elementaryschool 11 Jambu numbered 29 students. Instrument that use to observation test and observation. Technicanalysis the data used in this research is as statistically descriptive comparative. From analysis result on cycle Iis knowed percentage of mastery learning numbered 24 % by 7 students, experienced improve in cycle IInumbered 100 % by mastery learning 29 students. Conclusions based on the results of research a class act,learning by approaching play area cross game, can improve student learning for kanga escape.